The development of an integrated medical information system for Mary Johnston Hospital - Sandejas, Benedict N.A.I. (Animo Repository, 2004)
With the advancement of information technology in major businesses, it is important for medical institutions to begin utilizing Information Technology (IT) in storing and retrieving data. Hospitals mainly deal with chart files to store data which makes retrieval and interpretation of the data difficult when dealing with hundreds of files. The incorporation of IT into health institutions can simplify the repository of data which can then be easily accessed during the physicians decision making process. Mary Johnston Hospital is one such hospital. Mary Johnston has been around for decades and currently stores hundreds of files containing data that can be used in researches. The current system involves using folders to store data and log books to back up laboratory data. This makes retrieval of information for daily and monthly reports difficult, especially if some of the information is missing or incomplete. Physicians decisions on patient treatment are based on the ability to review laboratory results, radiology results, as well as older admission records. There is currently no such system in existence in the hospital. In order for such a system to function, multiple modules will have to be created, resulting in this study. This study has designed and evaluated a computerized Medical Information System (MIS) for Mary Johnston Hospital. This system is composed of six (6) modules, namely: Admission module, Medical Records module, Laboratory Records module, Radiology Records module, Medical Services module, and a System Administration module. The combined features of the six modules, comprising the MIS, are as follows: 1. The system can provide a data entry module for the Admission Section personnel for encoding new patient records and new admission records as well as give them access to former patient records 2. The system provides a data entry module for the Laboratory Section personnel to encode relevant data in the Laboratory Section 3. The system provides a data entry module for the Radiology Section personnel to encode relevant data in the Radiology Section; 4. The system provides a module that retrieve laboratory results, radiology results, and medical information of a single or multiple patient/s and make this data available to physicians in their respective departments; 5. The system provides a system capable of providing real-time information; and, 6. The system can generate necessary reports. In light of the systems features presented above, the proponent derived the following conclusions from the MIS that was designed: 1. The use of the evolutionary prototyping methodology is applicable in developing an integrated medical information system since it provides users unfamiliar with medical information systems a way to visualize the system, aiding in requirements analysis and design. 2. The application of a centralized database for all the departments eliminates redundancy of tasks performed by users of the system. Once information about admitted and not admitted patients is stored in the database, this information is accessible for access to any user running any module requiring the data. 3. The system allows physicians to view multiple tables containing laboratory results, radiology results, doctor orders, clinical abstract and clinical history reports within the confines of a single display, eliminating the problem of missing lab results and undecipherable notes. 4. The system simplifies the production of reports by accessing related tables in the database and retrieving needed information. 5. The results of the User Acceptance Test revealed a general weighted mean of 4.35, 4.91, 4.30, 4.54, and 4.63 for the Admission / Medical Records module, Laboratory records module, Radiology module, Medical Services module, and the System Administration module. Within the context of the results and conclusions, the proponent recommends the following: 1. The Integrated Information System of Mary Johnston can be further revised to include billing functions. 2. The integration of other records in the chart such as nurses notes, blood pressure monitoring sheets, and input output sheets can be designed and incorporated into the design. 3. The creation of modules for other hospital units such as the endoscopy unit, pulmonary unit, and the ECG unit can be created and integrated with the designed system. 4. The creation of a pharmacy information system that can allow doctors to view drug information and availability of these drugs in the pharmacy in the hospital. 5. The creation of new modules specifically for handheld devices running the palm or windows mobile operating systems which can allow doctors to access records at the patients bedside or anywhere else within the wireless network range.